Tomorrow's HR management : 48 thought leaders call for change - Ulrich, Dave (John Wiley New YorkUS, 1997)
Advocates strategic goals for human resource departments (HRDs). Includes topics such as: managing HRDs like businesses, with clear strategies, products, services and structure; preparing for challenges of the future such as new technology and globalization; playing new roles; and, creating work settings that treat employees humanely.